A magnetic core based on amorphous nanocrystalline soft magnetic particles and its preparation method and application

By using otoly nanocrystalline soft magnetic particles and coverage of FE-NI-SI-TI-AL particles, combined with Si-TI-AL composite oxide layer and TI-AL alloy layer, the existing inductive magnetic core is solved The problem of insufficient performance realizes high -performance, low power and stable magnetic core materials.

CN118782368BActive Publication Date: 2025-01-28广东泛瑞新材料股份有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410750289.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-12
Publication Date
2025-01-28
Estimated Expiration
2044-06-12

AI Technical Summary

Technical Problem

The existing inductor core made of soft magnetic alloy materials has problems such as low mechanical strength, low magnetic permeability, large inductance change rate, high power consumption and poor stability under high saturation magnetic field strength, which is difficult to meet the application needs of high-performance GPUs. .

Method used

The non-crystal nanocrystalline soft magnetic particles are used as a magnetic core material. The FE-Ni-Si-Ti-TI-AL material is converted into amorphous band materials through a single roller quenching method, and nanocrystalline particles are formed by two annealing treatment. At the same time, adding a meseped FE-Ni-Si-Ti-AL particles and silicon resin to improve the insulation performance and bonding effect through the Si-Ti-Al composite oxide layer and the Ti-Al alloy layer.

Benefits of technology

Improved the mechanical strength, magnetic guidance rate, low power consumption and high stability of the magnetic core, and suitable for the inductive magnetic core application for high -performance GPUs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004887671320000081
    Figure BDA0004887671320000081
Patent Text Reader

Abstract

The present invention discloses a magnetic core based on amorphous nanocrystalline soft magnetic particles, and a preparation method and application thereof. The preparation method of the magnetic core based on amorphous nanocrystalline soft magnetic particles of the present invention comprises the following steps: 1) melting Fe‑Ni‑Si‑Ti‑Al material into a melt; 2) subjecting the melt to rapid quenching treatment to make an amorphous strip; 3) subjecting the amorphous strip to two annealing treatments to make an amorphous nanocrystalline soft magnetic material; 4) crushing the amorphous nanocrystalline soft magnetic material to make an amorphous nanocrystalline soft magnetic particle; 5) mixing the amorphous nanocrystalline soft magnetic particles, the coated modified Fe‑Ni‑Si‑Ti‑Al particles and the silicone resin, and then pressing and sintering. The magnetic core based on amorphous nanocrystalline soft magnetic particles of the present invention has the advantages of high bending strength, high magnetic permeability, small inductance change rate under high saturation magnetic field intensity, low power consumption, and long-lasting and stable performance. It can be used as an inductor magnetic core in a graphics processor, and is suitable for large-scale industrial production and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of soft magnetic materials, and in particular to a magnetic core based on amorphous nanocrystalline soft magnetic particles and a preparation method and application thereof. Background Art

[0002] A graphics processing unit (GPU), also known as a display core, visual processor, or display chip, is a microprocessor that is specialized in performing image and graphics related operations on personal computers, workstations, game consoles, and some mobile devices (e.g., tablets, smartphones, etc.). GPUs require multiple inductor cores to ensure the stability and reliability of the power supply. As the computing power of GPUs increases exponentially, the operating current of GPUs continues to increase, the power becomes higher and higher, and the heat generated becomes greater and greater. People have also put forward higher performance requirements for inductor cores. However, existing inductor cores made of soft magnetic alloy materials generally have problems such as low strength, low magnetic permeability, large inductance change rate under high saturation magnetic field strength, high power consumption, and poor stability, which makes it difficult to fully meet the growing requirements of practical applications.

[0003] Therefore, it is of great significance to develop a soft magnetic material with high mechanical strength, high magnetic permeability, small inductance change rate under high saturation magnetic field intensity, low power consumption, and long-lasting and stable performance.

[0004] The above statements merely provide background information related to the present invention and do not necessarily constitute prior art. Summary of the invention

[0005] The object of the present invention is to provide a magnetic core based on amorphous nanocrystalline soft magnetic particles and a preparation method and application thereof.

[0006] The technical solution adopted by the present invention is:

[0007] A method for preparing a magnetic core based on amorphous nanocrystalline soft magnetic particles comprises the following steps:

[0008] 1) placing the Fe-Ni-Si-Ti-Al material in a protective atmosphere for smelting to obtain a melt;

[0009] 2) adding the melt into a vacuum single-roller spinning quenching machine for rapid quenching to obtain a Fe-Ni-Si-Ti-Al amorphous strip;

[0010] 3) placing the Fe-Ni-Si-Ti-Al amorphous strip in a protective atmosphere at a temperature of 500° C. to 550° C. for a first annealing treatment, and then heating the strip to 600° C. to 650° C. for a second annealing treatment to obtain an amorphous nanocrystalline soft magnetic material;

[0011] 4) crushing the amorphous nanocrystalline soft magnetic material to obtain amorphous nanocrystalline soft magnetic particles;

[0012] 5) The amorphous nanocrystalline soft magnetic particles, the coated modified Fe-Ni-Si-Ti-Al particles and the silicone resin are mixed, the composition of the coated modified Fe-Ni-Si-Ti-Al particles from the inside to the outside is Fe-Ni-Si-Ti-Al core, Si-Ti-Al composite oxide layer and Ti-Al alloy layer, and then pressed into shape, and then sintered in a protective atmosphere to obtain a magnetic core based on amorphous nanocrystalline soft magnetic particles.

[0013] Preferably, the Fe-Ni-Si-Ti-Al material in step 1) comprises the following components in weight percentage:

[0014] Fe: 45%~57.45%;

[0015] Ni: 40%~48%;

[0016] Si: 1.5%~3.5%;

[0017] Ti: 1.0%~3.0%;

[0018] Al: 0.05% to 0.5%.

[0019] Preferably, the protective atmosphere in step 1) is an argon atmosphere or a nitrogen atmosphere.

[0020] Preferably, the smelting in step 1) is carried out at a temperature of 1500° C. to 1600° C., the number of smelting is 3 to 5 times, and the time of a single smelting is 25s to 50s.

[0021] Preferably, the rapid quenching treatment in step 2) is carried out under the condition that the rotation speed of the cooling roller of the vacuum single-roller spinning quenching machine is 25m / s to 35m / s.

[0022] Preferably, in step 2), the thickness of the Fe—Ni—Si—Ti—Al amorphous strip is 25 μm to 50 μm.

[0023] Preferably, the protective atmosphere in step 3) is an argon atmosphere or a nitrogen atmosphere.

[0024] Preferably, the first annealing treatment in step 3) takes place for 10 to 20 minutes.

[0025] Preferably, the second annealing treatment in step 3) takes place for 5 to 10 minutes.

[0026] Preferably, the particle size of the amorphous nanocrystalline soft magnetic particles in step 4) is 20 μm to 50 μm.

[0027] Preferably, in step 5), the weight ratio of the amorphous nanocrystalline soft magnetic particles, the coated modified Fe-Ni-Si-Ti-Al particles, and the silicone resin is 1:0.7-1.2:0.04-0.08.

[0028] Preferably, the coated modified Fe-Ni-Si-Ti-Al particles in step 5) are prepared by a preparation method comprising the following steps:

[0029] a) smelting the Fe-Ni-Si-Ti-Al material, then performing ultra-high pressure water atomization, and then performing air flow classification to obtain Fe-Ni-Si-Ti-Al powder with a particle size of 3 μm to 50 μm;

[0030] b) mixing Fe-Ni-Si-Ti-Al powder and high temperature resistant oxide powder with a particle size of 0.1 μm to 1 μm, and treating the mixture at 400° C. to 600° C. in an atmosphere containing water vapor, and then removing the high temperature resistant oxide powder to obtain Fe-Ni-Si-Ti-Al particles containing a Si-Ti-Al composite oxide layer;

[0031] c) placing the Fe-Ni-Si-Ti-Al particles containing the Si-Ti-Al composite oxide layer in a reducing atmosphere for annealing to form a Ti-Al alloy layer on the surface of the Si-Ti-Al composite oxide layer, thereby obtaining coated and modified Fe-Ni-Si-Ti-Al particles.

[0032] Preferably, the Fe-Ni-Si-Ti-Al material in step a) comprises the following components in weight percentage:

[0033] Fe: 45%~57.45%;

[0034] Ni: 40%~48%;

[0035] Si: 1.5%~3.5%;

[0036] Ti: 1.0%~3.0%;

[0037] Al: 0.05% to 0.5%.

[0038] Preferably, the addition amount of the high temperature resistant oxide powder in step b) is 5% to 15% of the weight of the Fe-Ni-Si-Ti-Al powder.

[0039] Preferably, the high temperature resistant oxide powder in step b) is at least one of silicon oxide powder and aluminum oxide powder. The high temperature resistant oxide powder is distributed among the Fe-Ni-Si-Ti-Al powders, which can effectively prevent the Fe-Ni-Si-Ti-Al powders from sticking and agglomerating during the oxidation treatment.

[0040] Preferably, the water vapor-containing atmosphere in step b) consists of water vapor and at least one of air, nitrogen and argon.

[0041] Preferably, the volume percentage of water vapor in the water vapor-containing atmosphere in step b) is 70% to 90%.

[0042] Preferably, the treatment time in step b) is 1 h to 5 h.

[0043] Preferably, the reducing atmosphere in step c) is an atmosphere containing hydrogen.

[0044] Preferably, the annealing in step c) is carried out at 600° C. to 700° C., and the annealing time is 1 h to 3 h.

[0045] Preferably, the silicone resin in step 5) is at least one of silicone resin KR-220L produced by Shin-Etsu Chemical Co., Ltd., silicone resin KR-282 produced by Shin-Etsu Chemical Co., Ltd., and silicone resin KR-311 produced by Shin-Etsu Chemical Co., Ltd.

[0046] Preferably, the pressing pressure in step 5) is 20 tons / cm 2 ~25 tons / cm 2 .

[0047] Preferably, the protective atmosphere in step 5) is an argon atmosphere or a nitrogen atmosphere.

[0048] Preferably, the sintering in step 5) is carried out at a temperature of 500° C. to 550° C., and the sintering time is 0.5 h to 1.5 h.

[0049] A magnetic core based on amorphous nanocrystalline soft magnetic particles is made by the above preparation method.

[0050] A graphics processor comprises the magnetic core based on amorphous nanocrystalline soft magnetic particles.

[0051] An electronic product comprises the above-mentioned graphics processor.

[0052] Principle of the present invention:

[0053] 1) The present invention uses a single-roll spinning method to quickly convert the melt obtained by smelting the Fe-Ni-Si-Ti-Al material into an Fe-Ni-Si-Ti-Al amorphous strip, and then forms nanocrystals of different sizes in the Fe-Ni-Si-Ti-Al amorphous strip through a first annealing treatment (low temperature and long time), and then converts the nanocrystals of different sizes in the Fe-Ni-Si-Ti-Al amorphous strip into nanocrystals of smaller size and uniform size (refining of grains under the action of thermal stress) through a second annealing treatment (high temperature and short time), and the amorphous nanocrystal soft magnetic particles made of the amorphous nanocrystal soft magnetic material are used in the magnetic core to effectively improve the mechanical strength, magnetic permeability, power consumption and other properties of the magnetic core;

[0054] 2) The present invention adds coated and modified Fe-Ni-Si-Ti-Al particles in the magnetic core and utilizes the Si-Ti-Al composite oxide layer to improve the insulation performance of the magnetic core material, thereby reducing the eddy current loss between the particles, and utilizes the Ti-Al oxide film formed between the metal particles during the pressing and molding of the magnetic core material by the Ti-Al alloy layer to achieve the bonding of the metal particles, thereby avoiding the use of the traditional resin impregnation process, making the magnetic core less prone to aging problems, and ultimately making the magnetic core have the advantages of high mechanical strength, high magnetic permeability, small inductance change rate under high saturation magnetic field intensity, and long-lasting and stable performance.

[0055] The beneficial effects of the present invention are as follows: the magnetic core based on amorphous nanocrystalline soft magnetic particles of the present invention has the advantages of high bending strength, high magnetic permeability, small inductance change rate under high saturation magnetic field intensity, low power consumption, and long-lasting and stable performance. It can be used as an inductor core in a graphics processor and is suitable for large-scale industrial production applications. DETAILED DESCRIPTION

[0056] The present invention will be further explained and illustrated below in conjunction with specific embodiments.

[0057] Embodiment 1:

[0058] A magnetic core based on amorphous nanocrystalline soft magnetic particles, the preparation method of which is as follows:

[0059] 1) Fe-Ni-Si-Ti-Al material (composition: 57.45wt% Fe, 40wt% Ni, 1.5wt% Si, 1wt% Ti and 0.05wt% Al) was added into an electric arc furnace, and filled with nitrogen for protection, and then smelted 4 times at a temperature of 1520° C., with a single smelting time of 40s to obtain a melt;

[0060] 2) adding the melt into a vacuum single-roller spinning quenching strip spinning machine, adjusting the rotation speed (linear speed) of the cooling roll to 25 m / s for rapid quenching to obtain a Fe-Ni-Si-Ti-Al amorphous strip (thickness of 35 μm to 50 μm);

[0061] 3) placing the Fe-Ni-Si-Ti-Al amorphous strip in a nitrogen atmosphere at a temperature of 510° C. for 20 minutes of annealing, then heating to 620° C. for 10 minutes of annealing to obtain an amorphous nanocrystalline soft magnetic material;

[0062] 4) crushing the amorphous nanocrystalline soft magnetic material to obtain amorphous nanocrystalline soft magnetic particles (with a particle size of 30 μm to 50 μm);

[0063] 5) adding Fe-Ni-Si-Ti-Al material (composition: 57.45wt% Fe, 40wt% Ni, 1.5wt% Si, 1wt% Ti and 0.05wt% Al) into a high-frequency furnace for smelting, then performing ultra-high pressure water atomization, and then performing air flow classification to obtain Fe-Ni-Si-Ti-Al powder with a particle size of 3μm to 50μm; mixing the Fe-Ni-Si-Ti-Al powder with silicon oxide powder with a particle size of 0.1μm to 1μm in a weight ratio of 1:0.05, and then placing it in an argon- Treating the powder at 400°C for 1 hour in a water vapor mixed atmosphere (the volume ratio of argon to water vapor is 3:7), then sieving out the silicon oxide powder to obtain Fe-Ni-Si-Ti-Al powder containing a Si-Ti-Al composite oxide layer (particle size is 6 μm to 38 μm); annealing the Fe-Ni-Si-Ti-Al powder containing a Si-Ti-Al composite oxide layer at 600°C in a hydrogen atmosphere for 3 hours to form a Ti-Al alloy layer on the surface of the Si-Ti-Al composite oxide layer, thereby obtaining coated and modified Fe-Ni-Si-Ti-Al particles;

[0064] 6) The amorphous nanocrystalline soft magnetic particles, the coated modified Fe-Ni-Si-Ti-Al particles and the silicone resin (Silicone resin KR-220L of Shin-Etsu Chemical Co., Ltd.) were mixed uniformly in a weight ratio of 1:0.8:0.05, and then heated under a pressure of 20 tons / cm 2 The magnetic core based on amorphous nanocrystalline soft magnetic particles is obtained by pressing and molding under the conditions of , and then sintering at 500°C in an argon atmosphere for 1.5 hours.

[0065] Embodiment 2:

[0066] A magnetic core based on amorphous nanocrystalline soft magnetic particles, the preparation method of which is as follows:

[0067] 1) Fe-Ni-Si-Ti-Al material (composition: 51.2wt% Fe, 45wt% Ni, 2wt% Si, 1.5wt% Ti and 0.3wt% Al) was added into an electric arc furnace, and nitrogen was filled into the furnace for protection, and then smelted 4 times at a temperature of 1520° C., with a single smelting time of 45 s to obtain a melt;

[0068] 2) adding the melt into a vacuum single-roller spinning quenching strip spinning machine, adjusting the rotation speed (linear speed) of the cooling roll to 25 m / s for rapid quenching to obtain a Fe-Ni-Si-Ti-Al amorphous strip (thickness of 35 μm to 50 μm);

[0069] 3) placing the Fe-Ni-Si-Ti-Al amorphous strip in a nitrogen atmosphere at a temperature of 530° C. for 15 minutes, then heating it to 620° C. and annealing it for 5 minutes to obtain an amorphous nanocrystalline soft magnetic material;

[0070] 4) crushing the amorphous nanocrystalline soft magnetic material to obtain amorphous nanocrystalline soft magnetic particles (with a particle size of 30 μm to 50 μm);

[0071] 5) adding Fe-Ni-Si-Ti-Al material (composition: 51.2wt% Fe, 45wt% Ni, 2wt% Si, 1.5wt% Ti and 0.3wt% Al) into a high frequency furnace for smelting, then performing ultra-high pressure water atomization, and then performing air flow classification to obtain Fe-Ni-Si-Ti-Al powder with a particle size of 3μm to 50μm; mixing the Fe-Ni-Si-Ti-Al powder with alumina powder with a particle size of 0.1μm to 1μm in a weight ratio of 1:0.1, and then placing it in an air-water Treating the powder at 500°C for 3 hours in a steam mixed atmosphere (the volume ratio of air to water vapor is 1:9), then sieving out the alumina powder to obtain Fe-Ni-Si-Ti-Al powder containing a Si-Ti-Al composite oxide layer (particle size is 6 μm to 38 μm); annealing the Fe-Ni-Si-Ti-Al powder containing a Si-Ti-Al composite oxide layer at 650°C in a hydrogen atmosphere for 2 hours to form a Ti-Al alloy layer on the surface of the Si-Ti-Al composite oxide layer, thereby obtaining coated and modified Fe-Ni-Si-Ti-Al particles;

[0072] 6) Amorphous nanocrystalline soft magnetic particles, coated modified Fe-Ni-Si-Ti-Al particles and silicone resin (Silicone resin KR-220L of Shin-Etsu Chemical Co., Ltd.) were mixed uniformly in a weight ratio of 1:1:0.06, and then heated under a pressure of 22 tons / cm 2 The magnetic core based on amorphous nanocrystalline soft magnetic particles is obtained by pressing and molding under the conditions of , and then sintering at 500°C in an argon atmosphere for 1.5 hours.

[0073] Embodiment 3:

[0074] A magnetic core based on amorphous nanocrystalline soft magnetic particles, the preparation method of which is as follows:

[0075] 1) Fe-Ni-Si-Ti-Al material (composition: 45wt% Fe, 48wt% Ni, 3.5wt% Si, 3wt% Ti and 0.5wt% Al) was added into an electric arc furnace, and nitrogen was filled into the furnace for protection, and then smelted three times at a temperature of 1580° C., with a single smelting time of 50 s to obtain a melt;

[0076] 2) adding the melt into a vacuum single-roller spinning quenching strip spinning machine, adjusting the rotation speed (linear speed) of the cooling roll to 35 m / s for rapid quenching treatment, and obtaining a Fe-Ni-Si-Ti-Al amorphous strip (thickness of 25 μm to 35 μm);

[0077] 3) placing the Fe-Ni-Si-Ti-Al amorphous strip in a nitrogen atmosphere at a temperature of 550° C. for 10 minutes of annealing, then heating it to 650° C. for 5 minutes of annealing to obtain an amorphous nanocrystalline soft magnetic material;

[0078] 4) crushing the amorphous nanocrystalline soft magnetic material to obtain amorphous nanocrystalline soft magnetic particles (with a particle size of 20 μm to 35 μm);

[0079] 5) Fe-Ni-Si-Ti-Al material (composition: 45wt% Fe, 48wt% Ni, 3.5wt% Si, 3wt% Ti and 0.5wt% Al) is added into a high frequency furnace for smelting, and then ultra-high pressure water atomization is performed, and then air flow classification is performed to obtain Fe-Ni-Si-Ti-Al powder with a particle size of 3μm to 50μm; Fe-Ni-Si-Ti-Al powder and silicon oxide powder with a particle size of 0.1μm to 1μm are mixed uniformly in a weight ratio of 1:0.15, and then placed in a nitrogen-water steam furnace. The Fe-Ni-Si-Ti-Al powder containing the Si-Ti-Al composite oxide layer is annealed at 700° C. for 1 h in a hydrogen atmosphere to form a Ti-Al alloy layer on the surface of the Si-Ti-Al composite oxide layer, thereby obtaining coated and modified Fe-Ni-Si-Ti-Al particles;

[0080] 6) The amorphous nanocrystalline soft magnetic particles, the coated modified Fe-Ni-Si-Ti-Al particles and the silicone resin (Silicone resin KR-220L of Shin-Etsu Chemical Co., Ltd.) were mixed uniformly in a weight ratio of 1:1.2:0.08, and then heated under a pressure of 20 tons / cm 2 The magnetic core based on amorphous nanocrystalline soft magnetic particles is obtained by pressing and molding under the conditions of , and then sintering at 550°C in an argon atmosphere for 0.5h.

[0081] Embodiment 4:

[0082] A magnetic core based on amorphous nanocrystalline soft magnetic particles, the preparation method of which is as follows:

[0083] 1) Fe-Ni-Si-Ti-Al material (composition: 50.8wt% Fe, 45wt% Ni, 2wt% Si, 2wt% Ti and 0.2wt% Al) was added into an electric arc furnace, and nitrogen was filled into the furnace for protection, and then smelted 4 times at a temperature of 1550° C., with a single smelting time of 40 s to obtain a melt;

[0084] 2) adding the melt into a vacuum single-roller spinning quenching strip spinning machine, adjusting the rotation speed (linear speed) of the cooling roll to 30 m / s for rapid quenching treatment, and obtaining a Fe-Ni-Si-Ti-Al amorphous strip (thickness of 30 μm to 40 μm);

[0085] 3) placing the Fe-Ni-Si-Ti-Al amorphous strip in a nitrogen atmosphere at a temperature of 530° C. for 15 minutes, then heating it to 620° C. for 8 minutes to obtain an amorphous nanocrystalline soft magnetic material;

[0086] 4) crushing the amorphous nanocrystalline soft magnetic material to obtain amorphous nanocrystalline soft magnetic particles (with a particle size of 25 μm to 40 μm);

[0087] 5) Fe-Ni-Si-Ti-Al material (composition: 50.8wt% Fe, 45wt% Ni, 2wt% Si, 2wt% Ti and 0.2wt% Al) is added into a high frequency furnace for smelting, and then ultra-high pressure water atomization is performed, and then air flow classification is performed to obtain Fe-Ni-Si-Ti-Al powder with a particle size of 3μm to 50μm; Fe-Ni-Si-Ti-Al powder and silicon oxide powder with a particle size of 0.1μm to 1μm are mixed uniformly in a weight ratio of 1:0.1, and then placed in an argon-water vapor chamber. The Fe-Ni-Si-Ti-Al powder containing the Si-Ti-Al composite oxide layer is annealed at 650° C. for 2 h in a hydrogen atmosphere to form a Ti-Al alloy layer on the surface of the Si-Ti-Al composite oxide layer, thereby obtaining coated and modified Fe-Ni-Si-Ti-Al particles;

[0088] 6) Amorphous nanocrystalline soft magnetic particles, coated modified Fe-Ni-Si-Ti-Al particles and silicone resin (Silicone resin KR-220L of Shin-Etsu Chemical Co., Ltd.) were mixed uniformly in a weight ratio of 1:1:0.06, and then heated under a pressure of 20 tons / cm 2 The magnetic core based on amorphous nanocrystalline soft magnetic particles is obtained by pressing and molding under the conditions of , and then sintering at 520°C in an argon atmosphere for 1 hour.

[0089] Comparative Example 1: (Fe-Ni-Si-Ti-Al particles without coating modification)

[0090] A magnetic core, the preparation method of which is as follows:

[0091] Amorphous nanocrystalline soft magnetic particles (same as in Example 4) and silicone resin (Silicone resin KR-220L from Shin-Etsu Chemical Co., Ltd.) were mixed in a weight ratio of 1:0.03 and then heated under a pressure of 20 tons / cm 2 It is pressed into shape under the conditions of and then sintered at 520℃ in an argon atmosphere for 1h to obtain the magnetic core.

[0092] Comparative Example 2: (without amorphous nanocrystalline soft magnetic particles)

[0093] A magnetic core, the preparation method of which is as follows:

[0094] The coated modified Fe-Co-Si-Al particles (same as in Example 4) and silicone resin (Silicon resin KR-220L from Shin-Etsu Chemical Co., Ltd.) were mixed in a weight ratio of 1:0.03 and then heated under a pressure of 20 tons / cm 2It is pressed into shape under the conditions of and then sintered at 520℃ in an argon atmosphere for 1h to obtain the magnetic core.

[0095] Comparative Example 3: (Only single annealing treatment)

[0096] A magnetic core, the preparation method of which is as follows:

[0097] 1) placing the Fe-Ni-Si-Ti-Al amorphous strip (same as in Example 4) in a nitrogen atmosphere at a temperature of 530° C. for 15 min to obtain an amorphous nanocrystalline soft magnetic material;

[0098] 2) crushing the amorphous nanocrystalline soft magnetic material to obtain amorphous nanocrystalline soft magnetic particles (with a particle size of 25 μm to 40 μm);

[0099] 3) Amorphous nanocrystalline soft magnetic particles, coated modified Fe-Ni-Si-Ti-Al particles (same as in Example 4) and silicone resin (Silicone resin KR-220L from Shin-Etsu Chemical Co., Ltd.) were mixed uniformly in a weight ratio of 1:1:0.06, and then heated under a pressure of 20 tons / cm 2 It is pressed into shape under the conditions of and then sintered at 520℃ in an argon atmosphere for 1h to obtain the magnetic core.

[0100] Comparative Example 4: (Only single annealing treatment)

[0101] A magnetic core, the preparation method of which is as follows:

[0102] 1) placing the Fe-Ni-Si-Ti-Al amorphous strip (same as in Example 4) in a nitrogen atmosphere at a temperature of 620° C. for 8 min to obtain an amorphous nanocrystalline soft magnetic material;

[0103] 2) crushing the amorphous nanocrystalline soft magnetic material to obtain amorphous nanocrystalline soft magnetic particles (with a particle size of 25 μm to 40 μm);

[0104] 3) Amorphous nanocrystalline soft magnetic particles, coated modified Fe-Ni-Si-Ti-Al particles (same as in Example 4) and silicone resin (Silicone resin KR-220L from Shin-Etsu Chemical Co., Ltd.) were mixed uniformly in a weight ratio of 1:1:0.06, and then heated under a pressure of 20 tons / cm 2 It is pressed into shape under the conditions of and then sintered at 520℃ in an argon atmosphere for 1h to obtain the magnetic core.

[0105] Performance Test:

[0106] The performance test results of the magnetic cores of Examples 1 to 4 and Comparative Examples 1 to 4 are shown in the following table:

[0107] Table 1 Performance test results of the magnetic cores of Examples 1 to 4 and Comparative Examples 1 to 4

[0108]

[0109] Note:

[0110] Bending strength: The size of the test specimen is 35mm×4mm×3mm. It is tested on a universal testing machine with a test span of 30mm and a displacement loading rate of 0.5mm / min.

[0111] Magnetic permeability, inductance decrease rate and power consumption: The test sample is ring-shaped, with an outer diameter of 20mm, an inner diameter of 12mm, a height of 2mm, and the number of winding turns N=13Ts. The 3260B LCR tester is used to test the initial magnetic permeability μi (1V / 1MHz) of the magnetic ring sample, and the inductance decrease rate under the equivalent magnetic field intensity of a DC field H of 100Oe relative to when H is 0Oe is tested. The IWATSU-SY-8218 hysteresis loop meter is used to test the power consumption (50mT / 300kHz).

[0112] From Table 1, we can see that:

[0113] 1) The magnetic cores of Examples 1 to 4 have high bending strength, high magnetic permeability, small inductance change rate under high saturation magnetic field strength, low power consumption, and long-lasting and stable performance, and are suitable for use as inductor magnetic cores in graphics processors;

[0114] 2) The bending strength and magnetic permeability of the magnetic core of Comparative Example 1 (without adding the coated modified Fe-Ni-Si-Ti-Al particles) and the magnetic core of Comparative Example 2 (without adding the amorphous nanocrystalline soft magnetic particles) are significantly lower than those of the magnetic core of Example 4, and the inductance change rate is larger and the power consumption is higher under high saturation magnetic field strength, and the performance stability is much worse, indicating that the coated modified Fe-Ni-Si-Ti-Al particles and the amorphous nanocrystalline soft magnetic particles work synergistically and are indispensable;

[0115] 3) The bending strength and magnetic permeability of the magnetic core of Comparative Example 3 (the amorphous nanocrystalline soft magnetic material was only subjected to a single annealing treatment during preparation) and the magnetic core of Comparative Example 4 (the amorphous nanocrystalline soft magnetic material was only subjected to a single annealing treatment during preparation) were significantly lower than those of the magnetic core of Example 4, and the inductance change rate was greater and the power consumption was higher under high saturation magnetic field strength, and the performance stability was much worse, indicating that two different annealing treatments (the first annealing treatment was at a lower temperature and a longer time, while the second annealing treatment was at a higher temperature and a shorter time) were crucial for refining the grains in the amorphous nanocrystalline soft magnetic material.

[0116] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a magnetic core based on amorphous nanocrystalline soft magnetic particles, characterized in that: The following steps are involved: 1) The Fe-Ni-Si-Ti-Al material is placed in a protective atmosphere for smelting to obtain a melt; 2) adding the melt into a vacuum single-roller spinning quenching machine for rapid quenching to obtain Fe-Ni-Si-Ti-Al amorphous strip; 3) placing the Fe-Ni-Si-Ti-Al amorphous strip in a protective atmosphere at a temperature of 500°C to 550°C for a first annealing treatment, and then heating it to 600°C to 650°C for a second annealing treatment to obtain an amorphous nanocrystalline soft magnetic material; 4) crushing the amorphous nanocrystalline soft magnetic material to obtain amorphous nanocrystalline soft magnetic particles; 5) Amorphous nanocrystalline soft magnetic particles, coated modified Fe-Ni-Si-Ti-Al particles and silicone resin are mixed, the coated modified Fe-Ni-Si-Ti-Al particles are composed of Fe-Ni-Si-Ti-Al core, Si-Ti-Al composite oxide layer and Ti-Al alloy layer from inside to outside, and then pressed into shape, and then placed in a protective atmosphere for sintering to obtain a magnetic core based on amorphous nanocrystalline soft magnetic particles; Step 3) The first annealing treatment takes 10 to 20 minutes. Step 3) The second annealing treatment time is 5min to 10min; Step 5) The coated modified Fe-Ni-Si-Ti-Al particles are prepared by a preparation method comprising the following steps: a) melting the Fe-Ni-Si-Ti-Al material, atomizing it with ultra-high pressure water, and then performing air flow classification to obtain Fe-Ni-Si-Ti-Al powder with a particle size of 3 μm to 50 μm; b) mixing Fe-Ni-Si-Ti-Al powder and high temperature resistant oxide powder with a particle size of 0.1 μm to 1 μm, treating the mixture at 400° C. to 600° C. in a water vapor atmosphere, and then removing the high temperature resistant oxide powder to obtain Fe-Ni-Si-Ti-Al particles containing a Si-Ti-Al composite oxide layer; c) The Fe-Ni-Si-Ti-Al particles containing the Si-Ti-Al composite oxide layer are placed in a reducing atmosphere for annealing to form a Ti-Al alloy layer on the surface of the Si-Ti-Al composite oxide layer, thereby obtaining coated and modified Fe-Ni-Si-Ti-Al particles.

2. The preparation method according to claim 1, characterized in that: Step 1) The Fe-Ni-Si-Ti-Al material comprises the following components in weight percentage: Fe: 45%~57.45%; Ni: 40%~48%; Si: 1.5%~3.5%; Ti: 1.0%~3.0%; Al:0.05%~0.5%。 3. The preparation method according to claim 1 or 2, characterized in that: Step 1) The smelting is carried out at a temperature of 1500° C. to 1600° C., the number of smelting is 3 to 5 times, and the time of a single smelting is 25 seconds to 50 seconds.

4. The preparation method according to claim 1 or 2, characterized in that: Step 2) The rapid quenching treatment is carried out under the condition that the rotation speed of the cooling roller of the vacuum single-roller spinning quenching machine is 25m / s to 35m / s; Step 2) The thickness of the Fe-Ni-Si-Ti-Al amorphous strip is 25μm to 50μm.

5. The preparation method according to claim 1 or 2, characterized in that: Step 4) The particle size of the amorphous nanocrystalline soft magnetic particles is 20 μm to 50 μm.

6. The preparation method according to claim 1 or 2, characterized in that: Step 5) The weight ratio of the amorphous nanocrystalline soft magnetic particles, the coated modified Fe-Ni-Si-Ti-Al particles, and the silicone resin is 1:0.7-1.2:0.04-0.

08.

7. A magnetic core based on amorphous nanocrystalline soft magnetic particles, characterized in that: Prepared by the preparation method according to any one of claims 1 to 6.

8. A graphics processor, characterized in that: A magnetic core based on amorphous nanocrystalline soft magnetic particles as claimed in claim 7.

9. An electronic product, characterized in that: A graphics processor comprising the graphics processor of claim 8.

Citation Information

Patent Citations

  • Fe / FeSiB composite magnetic powder core and preparation method thereof

    CN107958762A

  • Soft magnetic alloy, magnetic core and magnetic component

    JP2022077960A